2023
DOI: 10.3389/fmedt.2023.1128460
|View full text |Cite
|
Sign up to set email alerts
|

Continuous pH monitoring using a sensor for the early detection of anastomotic leaks

Michelle Huynh,
Ricky Tjandra,
Nour Helwa
et al.

Abstract: Anastomotic leaks (AL) and staple line leaks are a serious post-operative complication that can develop following bariatric surgery. The delay in the onset of symptoms following a leak usually results in reactive diagnostics and treatment, leading to increased patient morbidity and mortality, and a clinical and economic burden on both the patient and the hospital. Despite support in literature for pH as a biomarker for early detection of AL, the current methods of pH detection require significant clinician inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies showed that the pH value of the drain fluids only shows minimal fluctuations between pH 7 and 8. [52] The amylase, lipase and trypsin activity within this range is not affected by pH (Figure S10, Supporting Information). With regard to temperature-dependence, the trypsin and amylase sensors show a modest temperature dependence and slower reaction at room temperature compared to body temperature (e.g., 1.5 h instead of 1 h for levels of 100 U mL −1 amylase, and 3.5 h vs 1 h for 100 μg mL −1 trypsin), while the lipase sensor only shows clinically feasible reaction times at body temperature.…”
Section: Macromolecular Network Design and Performancementioning
confidence: 94%
“…Previous studies showed that the pH value of the drain fluids only shows minimal fluctuations between pH 7 and 8. [52] The amylase, lipase and trypsin activity within this range is not affected by pH (Figure S10, Supporting Information). With regard to temperature-dependence, the trypsin and amylase sensors show a modest temperature dependence and slower reaction at room temperature compared to body temperature (e.g., 1.5 h instead of 1 h for levels of 100 U mL −1 amylase, and 3.5 h vs 1 h for 100 μg mL −1 trypsin), while the lipase sensor only shows clinically feasible reaction times at body temperature.…”
Section: Macromolecular Network Design and Performancementioning
confidence: 94%